Individual factors determine landing impacts in rested and fatigued cheerleaders - Müller, Andreas; Rockenfeller, Robert; Aiyangar, Ameet K. (Frontiers in Sports and Active Living, 2024)
High vertical ground reaction forces (VGRF) during landings following acrobatic elements in artistic gymnastics is associated with trunk and lower extremity injury risk. As similar data regarding injury risk factors in cheerleading are scarce, the purpose of this study was to assess VGRF in pop-off dismounts of rested and fatigued flyers in cheerleaders. Fifteen German cheerleaders were recruited for this study, including seven female flyers and eight male bases. It was expected that performance would change in fatiguing athletes, potentially increasing the risk for injuries. However, neither the mean VGRF (rested: 6.0±1.9 BW, fatigued: 6.2±1.3 BW, overall range: 2.1–14.9 BW) nor the individual VGRF-time courses of the flyers changed significantly after the workout. Instead, we show that the flyers’ ability to land – but not the bases’ ability to catch – significantly influences the maximum and time-resolved impacts.